Evaluasi Pelaksanaan Program Rasailah Daku dalam Mengatasi Permasalahan Anak Jalanan oleh Dinas Sosial Kota Padang - Dwi Putri, Rini; Mubarak, Adil (Policy, Law and Political Research Center, 2024)
This study aims to determine the performance of the Rasailah Daku Program implemented by the Padang City Social Service. The research method used in this study is a descriptive qualitative method. The theory used is the theory of William N. Dunn about program evaluation indicators, namely: 1) Effectiveness; 2) Efficiency; 3) Adequacy; 4) Equity; 5) Responsiveness; and 6) Accuracy. Data were obtained through interviews, observations, and documentation. The results of the study indicate that the implementation of the Rasailah Daku Program has been effective in reducing the growth rate of street children in Padang City, but the objectives of the program implementation have not been optimal because program participants have returned to their activities on the streets.